Key Factors and Perspectives in Cost Accounting with Real-Time Patterns - Alhabeeb, Omar Khalid Abdulameer; A, Mohammed Ahmed Dhahi; Abdullah, Kareema Jasim (South Asian Journal of Social Sciences and Humanities, 2022)
Cost accounting term describe by chartered institute of management accountants (CIMA). Cost  accounting helpsthe company to calculate total cost details regarding the product so that according  to total Cost Company can fix the sale price of the product including profit margin percentage. Cost accounting can be of type standard, marginal, lean, activity based. Cost is the monetary term of a product that is set up by measuring its various internal costs including labor, material, overheads, etc. Costing is the technique to calculate the cost of the product by calculating various factors. Cost accounting is next to costing which relates and analyzes the various costing data and interpretsit to the management which helpsto improve the efficiency of the business by controlling the various problems that occur in the business. Cost accountancy is the art and science of the cost accountant. The main objective of cost accounting is to help the managerial personnel to make  decisions about the product sale price, control production cost, and maximize the profit ratio. Based upon the cost sheet cost accounting can decide the estimated cost or actual cost of the  product. Cost sheets include different types of costs incurred during the product manufacturing  process.
Keywords: Key factors; Cost accounting; Real-time patterns